Herbal Medicine and Skeletal Muscle Atrophy: From Basic Science to Translational Medicine - Seifi, Sima; Karimi, Afshin; Marjani, Abdoljalal; Maftooh, Mina; Ghorbani, Elnaz; Fiuji, Hamid; Ghayour-Mobarhan, Majid; Ferns, Gordon A; Khazaei, Majid; Hassanian, Seyed Mahdi; Avan, Amir (Current Traditional Medicine, 2025)
Muscle atrophy is the volume loss and strength of muscle and happens in various conditions, such as starvation, nerve cutting, cancer cachexia, heart failure, old age, and immobility. Muscle atrophy is increasing every year and is usually associated with a low quality of life. In the time of muscle atrophy, systems of proteolytic are turned on and muscle proteins are degraded, leading to the contraction of muscle fibers. However, the precise mechanisms involved in muscle atrophy, as well as effective treatments, remain to be investigated. The purpose of this article is to give an overview of the effectiveness of supplements, herbs, and herb bioactive compounds on muscle atrophy. The significant beneficial effects of some plants and plant-derived natural products, including curcumin, geranylgeraniol, resveratrol, soy protein, green tea, and coffee, on muscle atrophy are reviewed in this review article. According to clinical investigations, these natural products may positively affect the physical function of muscles, including hand grip strength and knee tension, weight-lifting capacity, muscle fatigue, time and distance traveled before feeling tired, mitochondrial function and average muscle fiber level. However, more clinical trials are necessary to explore the possible value of herbal agents on skeletal muscle atrophy.
Keywords: skeletal muscle atrophy